The Impact of Waste on Domestic Tourist Visits to Pengaradan Beach, Banten Province - Atmanti, Hastarini Dwi; Purwanti, Evi Yulia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
As an archipelago, Indonesia is surrounded by water. Pengaradan Beach in Banten Province is one of the beaches in Indonesia that has tourism potential. The charm of Pengaradan Beach is disturbed by the garbage scattered around the beach. Waste is dominated by inorganic waste, namely plastic waste. This study aims to analyze the impact of waste on domestic tourists visiting the beach. The respondents were taken purposefully with a total of 50 respondents. This study uses descriptive statistics to describe tourist visits. As for what we portray are the characteristics of the respondents, the condition of the facilities and infrastructure at Pengaradan Beach and how the respondent responds to these tourist attractions. Based on the distributed questionnaire, it shows that the majority of tourists who visit are students. The reason most respondents visited tourist areas was because the entry tickets were cheap, even though the facilities and infrastructure in the tourist areas were inadequate and less clean. The level of beach cleanliness is lacking due to the lack of trash cans, so that many visitors throw their trash carelessly. The majority of the waste that is thrown away is plastic waste from the supplies brought by visitors. Dirty coastal environment is one reason tourists don't want to visit this beach anymore.The existence of garbage around the beach reduces the charm of Pengaradan Beach. Tourists will not return to this place because of the lack of cleanliness of the tourist sites and the lack of cleanliness of facilities and infrastructure. Pengaradan Beach management needs to be improved by involving the role of the local government, because so far this beach is only managed by residents around tourist sites. Keywords: Pengaradan Beach, trash, tourists, tourist visits